Chapter 8 Technology and the future Advancing prospective technology assessment - Schmidt, Jan Cornelius (Taylor & Francis, 2021)
Technology Assessment (TA) is an interdisciplinary field that deals with emerging, technology-induced societal problems for the purpose of shaping technology and technological development. TA is a perfect case for problem-oriented interdisciplinarity at the science-society interface. This chapter goes further and sheds light on a specific approach in TA, namely Prospective Technology Assessment (ProTA), which includes critical-reflexive elements in a prospective or anticipatory assessment of science and technology in very early phases of new and emerging knowledge fields; in this light ProTA can also be seen as an assessment of science (Liebert/Schmidt 2010). ProTA complements and extends well-established methods of Technology Assessment that have been used in policy consultancy from the late 1960s on. Applications of this approach to the field of synthetic/systems biology illustrate interdisciplinary core elements of Prospective Technology Assessment. It turns out that the critical-reflexive concept of interdisciplinarity incorporated in ProTA can be regarded as meta-instrumentalist: Thus ProTA contributes to the self-critique and self-reflexivity of the science/technology system.